Trimester-specific plasma exosome microRNA expression profiles in preeclampsia. (16th September 2020) - Devor, Eric; Santillan, Donna; Scroggins, Sabrina; Warrier, Akshaya; Santillan, Mark
Abstract: Objective: To identify microRNAs (miRNAs) differentially expressed in plasma exosomes collected in women diagnosed with preeclampsia compared with women with uncomplicated pregnancies. Materials and methods: Exosomes were purified from plasma samples obtained at each trimester from four women subsequently diagnosed with preeclampsia and from five matched healthy controls. RNA was purified from the exosomes, and expression of 368 miRNAs was profiled using A-Set TaqMan low density array (TLDA). Results: One-third of the 368 miRNAs profiled are not expressed in exosomes. Further, those that are not expressed tend to be evolutionarily younger and have a significantly different mature sequence signature than do miRNAs that are expressed in exosomes. Among miRNAs that are expressed in exosomes, a total of eight ( miR-134, miR-196b, miR-302c, miR-346, miR-376c, miR-486-3p, miR-590-5p, and miR-618 ) were found to display statistically significant differential expression between women who developed preeclampsia as compared with those who did not. Moreover, half of these miRNAs ( miR-134, miR-376c, miR-486-3p, and miR-590-5p ) displayed statistically significant differential expression in the first trimester. Conclusions: Not all miRNAs are expressed in exosomes. Those that tend to be evolutionarily older and have a significantly different mature sequence signature than those that are not. A few exosome-expressed miRNAs do display expression patterns in women subsequently diagnosed with preeclampsia that are significantly different than in women having an uncomplicated and, among these, several appear in the first trimester. These miRNAs are potential early markers of preeclampsia risk.